2016
DOI: 10.1021/acs.jafc.5b05623
|View full text |Cite
|
Sign up to set email alerts
|

The Major Soybean Allergen Gly m Bd 28K Induces Hypersensitivity Reactions in Mice Sensitized to Cow’s Milk Proteins

Abstract: Reactions to soy have been reported in a proportion of patients with IgE-mediated cow's milk allergy (CMA). In this work, we analyzed if Gly m Bd 28K/P28, one of the major soybean allergens, is a cross-reactive allergen with cow milk proteins (CMP). We showed that P28 was recognized by IgE sera from CMA patients and activated human peripheral basophils degranulation. Moreover, IgE sera of mice exclusively sensitized to CMP recognized P28. Splenocytes from sensitized animals secreted IL-5 and IL-13 when incubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 50 publications
0
22
1
2
Order By: Relevance
“…Nonetheless, it has been demonstrated that some patients are intolerant to such products, suggesting the cross‐reactivity between soy and cow milk proteins. It was reported that the α‐subunit of beta‐conglycinin (Gly m 5.0101) from the vicilin‐like protein family, the G4 subunit of glycinin (Gly m 6.0401) from legumin‐like proteins, and, more recently, the cysteine protease P34 (Gly m Bd30K) and the globulin P28 (Gly m Bd28K) are involved in cross‐reactivity phenomena with bovine caseins (Rozenfeld and others ; Katz and others ; Smaldini and others ; Curciarello and others ; Candreva and others ; Candreva and others ).…”
Section: Cross‐reactivity Of Milk Allergensmentioning
confidence: 99%
“…Nonetheless, it has been demonstrated that some patients are intolerant to such products, suggesting the cross‐reactivity between soy and cow milk proteins. It was reported that the α‐subunit of beta‐conglycinin (Gly m 5.0101) from the vicilin‐like protein family, the G4 subunit of glycinin (Gly m 6.0401) from legumin‐like proteins, and, more recently, the cysteine protease P34 (Gly m Bd30K) and the globulin P28 (Gly m Bd28K) are involved in cross‐reactivity phenomena with bovine caseins (Rozenfeld and others ; Katz and others ; Smaldini and others ; Curciarello and others ; Candreva and others ; Candreva and others ).…”
Section: Cross‐reactivity Of Milk Allergensmentioning
confidence: 99%
“…Furthermore, Candreva et al analyzed the in silico similarity between proteins at the peptide level 5 . Cross‐reactivity between milk and soy proteins has been suggested by other immunologic studies 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Candreva et al analyzed the in silico similarity between proteins at the peptide level. 5 Crossreactivity between milk and soy proteins has been suggested by other immunological studies. 6 Thus, we also employed an in silico analysis at the peptide level using the peptide similarity tool on the Structural Database of Allergenic Proteins (SDAP).…”
Section: Introductionmentioning
confidence: 87%